Digitalisasi Pengelolaan Pojok Baca Kelas melalui Penerapan Senayan Library Management System (SLiMS) di RA Ulul Albab Kaliwates Jember - Dina Maulidatul Hasanah; Kamilatun Khoiriyah; Dani Hermawan (Lembaga Pengembangan Kinerja Dosen, 2026)
The management of the classroom reading corner at RA Ulul Albab Kaliwates Jember was previously conducted manually, resulting in disorganized book records, duplication, and data loss. This condition hindered the effectiveness of the reading corner as a medium for fostering early literacy habits. To address this issue, this study aims to digitalize reading corner management through the implementation of the Senayan Library Management System (SLiMS) to create a centralized, efficient, and accurate data recording system. This research employs an action research method using the Kemmis & McTaggart model, which consists of four stages: planning, acting, observing, and reflecting. The research subjects include school administrators, teachers, and students of RA Ulul Albab. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed both qualitatively and quantitatively using descriptive methods. The results show that SLiMS successfully improved the organization and accuracy of book records, increased data processing efficiency up to fivefold, and enhanced administrative transparency. Each book now has a digital identity that can be easily accessed through the system, facilitating supervision and reporting. Overall, the digitalization of the reading corner using SLiMS proved effective in strengthening digital literacy management and administrative efficiency in early childhood education institutions.